The most important elections you just missed - Mukherji, Rahul; Mander, Harsh; Zarhani, Seyed Hossein (Journal of democracy, 2023)
India just held five state elections that did more than declare winners and losers: They offered a roadmap for how to win the national contest in the world’s most populous democracy next year.